2017
DOI: 10.1002/jcb.26289
|View full text |Cite|
|
Sign up to set email alerts
|

Megakaryocytes Enhance Mesenchymal Stromal Cells Proliferation and Inhibit Differentiation

Abstract: Megakaryocytes (MKs) can induce proliferation of calvarial osteoblasts [Ciovacco et al., 2009], but this same phenomenon has not been reported for bone marrow stromal populations from long bones. Bone marrow contains several types of progenitor cells which can be induced to differentiate into multiple cell types. Herein, we examined mesenchymal stromal cell proliferation and osteoblastic differentiation when rabbit or mouse MK were cultured with i) rabbit bone marrow stromal cells, ii) rabbit dental pulp strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…RT‐qPCR found that c‐Fos expression increased threefold in the loaded limb compared with the contralateral unloaded control limb, which is similar to the response of osteocytes . Multiple in vitro studies have shown that megakaryocytes affect osteoblast and osteoclast differentiation and activity . Interestingly, when megakaryocytes were exposed to fluid shear, the conditioned media inhibited osteogenesis in the MC3T3 osteoblast cell line .…”
Section: The Response Of Bone Marrow Cells To Mechanical Loadsmentioning
confidence: 65%
See 1 more Smart Citation
“…RT‐qPCR found that c‐Fos expression increased threefold in the loaded limb compared with the contralateral unloaded control limb, which is similar to the response of osteocytes . Multiple in vitro studies have shown that megakaryocytes affect osteoblast and osteoclast differentiation and activity . Interestingly, when megakaryocytes were exposed to fluid shear, the conditioned media inhibited osteogenesis in the MC3T3 osteoblast cell line .…”
Section: The Response Of Bone Marrow Cells To Mechanical Loadsmentioning
confidence: 65%
“…Individual bone marrow–resident cells have been studied in in vitro culture and subjected to mechanical loads, demonstrating that the relevant cells are mechanosensitive. Coculture has further demonstrated that both mesenchymal and hematopoietic lineage cells in the marrow interact with osteocytes and osteoblast precursors through various signaling pathways . While understanding bone marrow response as a tissue has proven challenging, a seminal in vitro study of bone marrow aliquots subjected to compressive load and another novel in vivo study based on bone marrow transplantation have allowed us to separate mechanobiological signaling from osteocytes from that of marrow to identify potential biological pathways and cellular structures that affect bone adaptation through mechanical stimuli acting in the marrow cavity …”
Section: Bone Mechanobiologymentioning
confidence: 99%
“…BMSCs are adult multipotent stem cells derived from bone marrow tissue [ 47 ]. BMSCs are a promising cell source due to their self-renewal and multipotency by differentiating into different cell types, such as osteoblasts, chondrocytes, and adipocytes [ 125 , 206 , 209 , 223 , 224 , 225 , 226 , 227 , 228 , 229 ]. BMSCs are attractive MSCs that have high therapeutic potential.…”
Section: Mesenchymal Stromal Cells: Successes and Challengesmentioning
confidence: 99%
“…However, whether or not MKs can facilitate MSCs proliferation and differentiation to regenerate cranial bone defects is a question yet to be addressed. Particularly, the effects of increasing MK count to enhance viability and differentiation of BMSCs or DPSCs in vivo for cranial bone tissue engineering purposes has not been determined [ 125 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation